A mixed‐methods approach to improve the measurement of alcohol‐induced blackouts: ABOM‐2. (30th June 2022) - Boness, Cassandra L.; Gatten, Natalie; Treece, Mc Kenna; Miller, Mary Beth
Abstract: Background: Alcohol‐induced blackouts describe memory loss resulting from alcohol consumption. Approximately half of college students report experiencing a blackout in their lifetime. Blackouts are associated with an increased risk for negative consequences, including serious injury. Research has documented two types of blackouts, en bloc (EB) and fragmentary (FB). However, research is limited by the lack of a validated measure that differentiates between these two forms of blackout. This study used a mixed‐methods approach to improve the assessment of FB and EB among young adults. Specifically, we sought to improve the existing Alcohol‐Induced Blackout Measure (ABOM), which was derived from a relatively small pool of items that did not distinguish FB from EB. Methods: Study 1 used three rounds of cognitive interviewing with U.S. college students ( N  = 31) to refine existing assessment items. Nineteen refined blackout items were retained for Study 2. Study 2 used face validity, factor analysis, item response theory, and external validation analyses to test the two‐factor blackout model among U.S. heavy‐drinking college students ( N  = 474) and to develop and validate a new blackout measure (ABOM‐2). Results: Iterative factor analyses demonstrated that the items were well represented by correlated EB and FB factors, consistent with our hypothesis. External validation analyses demonstrated convergent and discriminant validity. These analyses also provided preliminary evidence for the two factors having differential predictive validity (e.g., FB correlated with enhancement drinking motives, while EB correlated with coping and conformity motives). Conclusions: The Alcohol‐Induced Blackout Measure‐2 (ABOM‐2) improves the measurement of blackout experiences among college students. Its use could facilitate the examination of EB and FB as differential predictors of alcohol‐related outcomes in future studies. Abstract : Alcohol‐induced blackout is often measured with a single item or narrow set of items which fails to adequately assess both fragmentary and en bloc blackouts. Study 1 and Study 2 used mixed methods to refine the measurement of alcohol‐induced blackouts and stringently test the hypothesized two‐factor structure. The new 8‐item scale offers more coverage in the assessment of alcohol‐induced blackouts as well as additional precision in examining associations with relevant correlates, particularly among college students.